Polymer self-repairing material and preparation method thereof
By constructing a multi-layer network structure of epoxy resin with cross-link density gradient and distributing self-healing microcapsules and anti-aging agents in each layer, the problem of insufficient repair ability of polymer self-healing materials in the prior art is solved, and efficient and multiple self-healing effects are achieved.
Patent Information
- Application Number
- CN202411226465.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After multiple repairs, the repair agent distribution of existing polymer self-healing materials is uneven, and the content of repair agents in the microcapsules is limited, so it is impossible to achieve multiple self-healing of the material, and there are few reaction sites on the healing surface, resulting in a decrease in self-healing efficiency.
A multi-layer network structure is constructed by layer-by-layer self-assembly technology using an epoxy resin layer with a cross-link density from low to high. Each epoxy resin layer contains self-healing microcapsules and anti-aging agents, which enhance fillers such as carbon fiber or glass fiber are used to improve stress dispersion and stress absorption capabilities.
It realizes repeated repair of polymer self-repair materials in damaged areas, improves repair efficiency and effect, extends the service life of the material, and reduces maintenance costs.
Smart Images

Figure CN119116516B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer self-repairing materials, and in particular to polymer self-repairing materials and preparation methods thereof. Background Art
[0002] Polymer self-healing materials, also known as self-repairing materials, refer to a new type of material that can self-repair after being damaged. These materials can recognize the occurrence of damage and immediately self-repair, thereby ensuring the reliability of the material, reducing the maintenance cost of the item and extending the service life of the item.
[0003] According to the different repair mechanisms, researchers divide self-healing materials into four generations in chronological order: the first generation uses external repair agents to achieve self-repair (external mechanism). This material can only be repaired once. Due to the limited content of the repair agent inside the microcapsule, it does not have the recycling function and cannot achieve multiple self-repair of the material. Moreover, the area where the microcapsule is located exists in the form of "voids" after repair, which increases the hidden dangers of material structural defects; the second generation uses reversible chemical bonds to achieve self-repair (internal mechanism), but the performance cannot be fully restored. When the material is repeatedly damaged, there are very few reaction sites on the healable surface, resulting in insufficient diffusion of molecular chains. After each cutting and healing cycle, the self-healing efficiency decreases slightly; the third generation also uses external repair agents, but the repair agents are distributed in the polymer network (external mechanism). The third generation of self-healing polymers can achieve multiple repairs, but the repair agents are unevenly distributed in the polymer network; the fourth generation is based on multiple repair mechanisms to achieve efficient repair, multiple repairs, and better mechanical properties of the repaired material. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, one of the purposes of the present invention is to provide a polymer self-healing material, the damaged part of the polymer self-healing material can be repeatedly repaired, the damaged part has many reaction sites on the healing surface, and the self-healing microcapsules in other areas of the material can supplement the deficiencies of the damaged part, so that the crack repair efficiency of the damaged part is high and the repair effect is good.
[0005] A second object of the present invention is to provide a method for manufacturing a polymer self-healing material, which has simple steps and low cost.
[0006] One of the purposes of the present invention is achieved by the following technical solution:
[0007] The polymer self-healing material has a multi-layer network structure constructed by layer-by-layer self-assembly technology of epoxy resin layers with cross-linking density from low to high. Each epoxy resin layer contains self-healing microcapsules and anti-aging agents, and the epoxy resin layer with the highest cross-linking density contains reinforcing fillers and compatibilizers.
[0008] Furthermore, the reinforcing filler is carbon fiber or glass fiber.
[0009] Furthermore, the compatibilizer is DH-2.
[0010] Furthermore, the epoxy resin layer is formed by the cross-linking reaction of diepoxybutane and cystamine, each layer of the network structure is an epoxy resin layer, the epoxy resin layer with the highest cross-linking density is the outer layer of the multi-layer network structure, and the epoxy resin layer with the highest cross-linking density is formed by the cross-linking reaction of diepoxybutane and cystamine at 50-55°C, and the reaction condition is that the molar ratio of the diepoxybutane to the cystamine is 1:1; from the outer layer to the inner layer of the multi-layer network structure, the epoxy resin layer is also formed by the reaction of the diepoxybutane and the cystamine at 50-55°C, and the molar ratio of the diepoxybutane to the cystamine is greater than 1:1 layer by layer, and the cross-linking density of the formed epoxy resin layer decreases layer by layer.
[0011] Furthermore, the self-repairing microcapsules are evenly dispersed in each epoxy resin layer.
[0012] Furthermore, in each epoxy resin layer, the self-repairing microcapsules are prepared by an in-situ polymerization method, and the specific preparation steps are as follows:
[0013] S1, first preparing a urea-formaldehyde resin prepolymer, mixing urea and formaldehyde in proportion, reacting at a pH value of 3 and a temperature of 90° C. for 1 hour to form the urea-formaldehyde resin prepolymer;
[0014] S2, using hydroxy silicate as the core material, dispersing it in water, adding an emulsifier, and forming an aqueous solution;
[0015] S3, using diepoxybutylene as the oil phase solution, and slowly adding the water phase solution to the oil phase solution under stirring to emulsify and form a water-in-oil emulsion;
[0016] S4. Add the urea-formaldehyde resin prepolymer to the water-in-oil emulsion, add a curing agent, adjust the pH value of the solution to an alkaline environment to promote the cross-linking reaction of the urea-formaldehyde resin prepolymer itself, maintain the reaction at a temperature of 60° C., and form the self-healing microcapsules in the diepoxybutylene solution.
[0017] Furthermore, after the self-repairing microcapsules are formed in the diepoxybutane solution, the cystamine is added to the diepoxybutane solution according to the molar ratio of the diepoxybutane to the cystamine, stirred evenly, and a cross-linking reaction is carried out at 50-55° C. to obtain each epoxy resin layer.
[0018] The second object of the present invention is achieved by adopting the following technical solution:
[0019] The method for preparing a polymer self-repairing material comprises the following steps:
[0020] S1, immersing the base material in an ionic emulsifier solution to pretreat the base material to obtain a pretreated base material;
[0021] S21, first preparing a urea-formaldehyde resin prepolymer, mixing urea and formaldehyde in proportion, reacting at a pH value of 3 and a temperature of 90° C. for 1 hour to form the urea-formaldehyde resin prepolymer;
[0022] S22, using hydroxy silicate as a core material, dispersing it in water, adding sodium dodecyl sulfate (SDS) or dodecyl ammonium sulfate (DTAB) to form an aqueous solution;
[0023] S23, using diepoxybutylene as the oil phase solution, slowly adding the aqueous phase solution into the aqueous phase solution under stirring conditions, emulsifying to form a water-in-oil emulsion;
[0024] S24, adding the urea-formaldehyde resin prepolymer to the water-in-oil emulsion, adding a curing agent, adjusting the pH value of the solution to an alkaline environment to promote the cross-linking reaction of the urea-formaldehyde resin prepolymer, maintaining the reaction at a temperature of 60° C., and forming the self-healing microcapsules in the diepoxybutylene solution;
[0025] S25, adding the cystamine to the diepoxybutane solution according to the molar ratio of the diepoxybutane to the cystamine, and adding the anti-aging agent, stirring evenly, the molar ratio of the diepoxybutane to the cystamine is greater than 1:1; then immersing the pretreated substrate material in the solution, performing a cross-linking reaction at 50-55° C., curing to form a first layer of the epoxy resin layer on the pretreated substrate material, and washing unreacted diepoxybutane;
[0026] S3. According to the preparation method of the first epoxy resin layer, continue to prepare the second epoxy resin layer, and form a multi-layer epoxy resin layer through electrostatic self-assembly until the outer layer of the multi-layer network structure. The method for preparing the outer layer of the multi-layer network structure is different from the preparation method of the first epoxy resin layer in that, in step S25, after adding the anti-aging agent, the reinforcing filler and the compatibilizer are added, and the mixture is stirred evenly, and the molar ratio of the diepoxybutane to the cystamine is 1:1; then continue to immerse the base material in the solution, and perform a cross-linking reaction at 50-55°C to form the outer layer of the multi-layer network structure on the base material, and wash the unreacted diepoxybutane to obtain the polymer self-healing material.
[0027] Furthermore, in step S22, a thiol oxidant can be added and dispersed in water together with the hydroxy silicate as a core material.
[0028] Furthermore, the base material is metal, wood or plastic.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The polymer self-repairing material provided by the present invention, the reinforcing filler such as carbon fiber or glass fiber can significantly improve the stress dispersion and stress absorption capacity of the surface of the polymer self-repairing material, which is helpful to reduce the formation and diffusion of surface cracks. After the reinforcing filler is treated with DH-2, the dispersibility of the reinforcing filler in the epoxy resin can be improved, and the compatibility of the reinforcing filler and the epoxy resin can be improved, so that the reinforcing filler can fully play its role; cystamine is a compound containing disulfide bonds, and each layer of the prepared epoxy resin layer contains reversible disulfide bonds, and the reversible disulfide bonds can undergo multiple cycles of breaking and reorganization, which provides multiple repairs for the polymer self-repairing material. The invention has the advantages of high cross-linking density, high self-repairing ability, and the multi-layer network structure is constructed by layer-by-layer self-assembly technology of epoxy resin layers with cross-linking density from low to high. The self-repairing microcapsules are evenly dispersed in each epoxy resin layer. When the material is damaged, the self-repairing microcapsules at the damaged part are broken under the action of stress, and the self-repairing microcapsules at other positions of the damaged part and other epoxy resin layers can still be easily migrated to the damaged part, thereby improving the repair efficiency and repair effect of the self-repairing microcapsules at the damaged part; each epoxy resin layer contains an anti-aging agent, which slows down the aging of the material during repeated damage and repair cycles, and improves the repair efficiency of the reversible disulfide bond to achieve self-repair.
[0031] The polymer self-healing material provided by the present invention comprises a self-healing microcapsule with hydroxy silicate and a thiol oxidant as core materials, each epoxy resin layer is formed by reacting diepoxybutane and cystamine at 50-55° C., the diepoxybutane contains two epoxy groups, and the two ends of the cystamine contain two amino groups, each amino group reacts with an epoxy group, and the obtained epoxy resin molecular chain can directly form a network structure through cystamine cross-linking, and no additional curing agent for the epoxy resin molecular chain is required, and the epoxy group forms a hydroxyl group after ring opening, and the hydroxy silicate can react with the hydroxyl group to increase the reaction sites of the healable surface of the damaged part, thereby improving the repair efficiency of the reversible disulfide bonds in the epoxy resin and strengthening the repair effect of the reversible disulfide bonds, and the self-healing microcapsule can also contain a thiol oxidant, which can catalyze the formation of disulfide bonds and improve the repair efficiency of the reversible disulfide bonds. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0033] Figure 1 It is a microscopic observation picture of the self-healing results of the iron sheet materials provided in Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0035] 1,2,3,4-Diepoxybutane was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. ,CAS:298-18-0.
[0036] Example 1
[0037] The polymer self-repairing material provided in this embodiment is a multi-layer network structure constructed by layer-by-layer self-assembly technology of epoxy resin layers with cross-linking density from low to high, each epoxy resin layer contains self-repairing microcapsules and anti-aging agent butylated hydroxytoluene, the epoxy resin layer with the highest cross-linking density contains reinforcing filler carbon fiber and compatibilizer DH-2, and the self-repairing microcapsules contain hydroxy silicate. Butylated hydroxytoluene is a bisphenol A type antioxidant, which can delay or inhibit the degradation process of the material due to the action of atmospheric oxygen during polymerization, storage, transportation, processing, and use, thereby preventing material aging and extending the service life.
[0038] The epoxy resin layer is formed by the cross-linking reaction of diepoxybutane and cystamine, each layer of the network structure is an epoxy resin layer, the epoxy resin layer with the highest cross-linking density is the outer layer of the multi-layer network structure, and the epoxy resin layer with the highest cross-linking density is formed by the cross-linking reaction of diepoxybutane and cystamine at 50-55°C, and the reaction condition is that the molar ratio of diepoxybutane to cystamine is 1:1; from the outer layer to the inner layer of the multi-layer network structure, the epoxy resin layer is also formed by the reaction of diepoxybutane and cystamine at 50-55°C, and the molar ratio of diepoxybutane to cystamine is greater than 1:1 layer by layer, and the cross-linking density of the formed epoxy resin layer decreases layer by layer.
[0039] The method for preparing the polymer self-healing material provided in this embodiment comprises the following steps:
[0040] S1. Using an iron sheet as a substrate material, immersing the iron sheet in a dodecyl ammonium sulfate (DTAB) solution, where dodecyl ammonium sulfate is a cationic emulsifier that dissociates in water to form a positively charged substance, pretreating the iron sheet so that the surface of the iron sheet is positively charged, thereby obtaining a pretreated iron sheet;
[0041] S21, firstly prepare a urea-formaldehyde resin prepolymer, mix urea and formaldehyde in a molar ratio of 1:2, react under the conditions of pH 3 and temperature of 90°C for 1 hour to form a urea-formaldehyde resin prepolymer, the urea-formaldehyde resin prepolymer is a white precipitate of methylene urea, which is generated by the reaction of urea and formaldehyde. The prepared urea-formaldehyde resin prepolymer is very turbid and unstable, and cannot be cross-linked to obtain a water-insoluble polymer;
[0042] S22, using hydroxy silicate as the core material, dispersing it in water, adding sodium dodecyl sulfate (SDS) or ammonium dodecyl sulfate (DTAB) to form an aqueous solution; sodium dodecyl sulfate is an anionic emulsifier, which dissociates in water to form a negative charge; ammonium dodecyl sulfate is a cationic emulsifier, which dissociates in water to form a positive charge;
[0043] S23, diepoxybutylene as the oil phase solution, under stirring conditions, slowly adding the aqueous phase solution to the oil phase solution for emulsification to form a water-in-oil emulsion;
[0044] S24, adding urea-formaldehyde resin prepolymer to a water-in-oil emulsion, and adding a curing agent, resorcinol, adjusting the pH value of the solution to 8 to promote the cross-linking reaction of the urea-formaldehyde resin prepolymer itself, maintaining the reaction at a temperature of 60° C., forming self-repairing microcapsules in a diepoxybutane solution, and the unstable urea-formaldehyde resin prepolymer generates stable water-soluble hydroxymethyl urea in an alkaline environment. The prepared urea-formaldehyde resin prepolymer is viscous and transparent, and the hydroxymethyl urea contains hydroxymethyl and imino groups. The core material is continuously polycondensed to obtain a non-water-soluble polymer with a cross-linked network structure, thereby obtaining a self-repairing microcapsule;
[0045] S25, adding cystamine to the diepoxybutane solution according to a molar ratio of diepoxybutane to cystamine of 5:1, and adding butyl hydroxytoluene (an anti-aging agent), stirring evenly, then immersing the pretreated iron sheet in the solution, performing a cross-linking reaction at 50° C., curing to form a first epoxy resin layer on the pretreated iron sheet, and washing unreacted diepoxybutane;
[0046] S3, according to the preparation method of the first epoxy resin layer, continue to prepare the second epoxy resin layer, when the two adjacent epoxy resin layers are prepared, the emulsifier added in step S22 needs to have opposite electrical properties, the emulsifier dissociates in water, and the emulsified product also carries corresponding positive or negative charges, each layer of epoxy resin after cross-linking also carries corresponding positive or negative charges due to network adsorption and other effects, each layer of epoxy resin self-assembles through electrostatic action to form a multi-layer epoxy resin layer until the outer layer of the multi-layer network structure, the electrostatic self-assembly effect is specifically: when the base material is positively charged after pretreatment, the preparation method of the first epoxy resin layer step S22 uses a negatively charged anionic emulsifier, then the preparation method of the second epoxy resin layer In step S22, a cationic emulsifier with a positive charge is used, and so on until the outer layer of the multi-layer network structure, each epoxy resin layer self-assembles through electrostatic action to form a multi-layer network structure; the preparation method of the outer layer is different from that of the first epoxy resin layer. The preparation method of the outer layer of the multi-layer network structure is that in step S25, after adding the anti-aging agent butylhydroxytoluene, reinforcing filler carbon fiber and compatibilizer DH-2 are added, and stirred evenly, the molar ratio of diepoxybutane to cystamine is 1:1, and then the iron sheet is immersed in the solution, and a cross-linking reaction is carried out at 50°C to form an outer layer of the multi-layer network structure on the iron sheet material, and the unreacted diepoxybutane is washed and dried to obtain a polymer self-healing material.
[0047] Each epoxy resin layer is formed by the reaction of diepoxybutane and cystamine at 50°C. Dipoxybutane contains two epoxy groups, and the two ends of cystamine contain two amino groups. Each amino group reacts with an epoxy group, and the resulting epoxy resin molecular chain can directly form a network structure through cystamine cross-linking. It can be seen that when the molar ratio of diepoxybutane to cystamine is 1:1, diepoxybutane and cystamine react completely, and the cross-linking density of the formed epoxy resin layer is the highest. When the molar ratio of diepoxybutane to cystamine is greater than 1:1 layer by layer, the cross-linking density of the formed epoxy resin layer decreases layer by layer, forming an epoxy resin layer with a cross-linking density from low to high, and the multi-layer network structure is formed by cross-linking. The epoxy resin layers with density from low to high are constructed through layer-by-layer self-assembly technology. The self-repairing microcapsules are evenly dispersed in each epoxy resin layer. When the surface of the iron sheet is damaged, cracks are generated at the damaged part, and the self-repairing microcapsules rupture under the stress. The self-repairing microcapsules at other positions of the damaged part and other epoxy resin layers can still easily migrate to the damaged part, thereby improving the repair efficiency and repair effect of the self-repairing microcapsules at the damaged part. Therefore, it can solve the problem that the third-generation self-repairing polymer can achieve multiple repairs, but the repair agent is unevenly distributed in the polymer network, the content of the repair agent inside the microcapsule is limited, and it does not have the recycling function, and cannot achieve multiple self-repair of the material. Reinforcing fillers such as carbon fiber can significantly improve the stress dispersion and stress absorption capacity of the epoxy resin layer with the highest cross-linking density in the polymer self-healing material, which helps to reduce the formation and diffusion of surface cracks at the damaged part. After the reinforcing filler is treated with DH-2, the dispersion of the reinforcing filler carbon fiber in the epoxy resin can be improved, and the compatibility of the reinforcing filler carbon fiber and the epoxy resin can be improved, so that the reinforcing filler carbon fiber can increase the mechanical strength of the damaged surface, reduce the brittleness of the material caused by excessive cross-linking, improve the flexibility of the material, make it less likely to crack on the material surface, and the speed at which cracks form will also be slow.
[0048] In addition, the epoxy group forms a hydroxyl group after ring opening, and the hydroxy silicate can react with the hydroxyl group to increase the reaction sites of the healing surface of the damaged part, improve the repair efficiency of the reversible disulfide bonds in the epoxy resin, and strengthen the repair effect of the reversible disulfide bonds. Therefore, it can solve the problem that when the material is repeatedly damaged, there are few reaction sites on the healing surface, resulting in insufficient diffusion of the molecular chain, and the self-healing efficiency decreases slightly after each cutting and healing cycle.
[0049] The water phase is used as the dispersed phase and the oil phase is used as the continuous phase. The emulsifier is added to the water phase, and then the water phase is dispersed into the oil phase by stirring or high shear force. During the emulsification process, the water droplets are surrounded by the emulsifier and dispersed in the oil phase to form smaller water droplets. The in-situ polymerization method is to add all the reactive monomers (or their soluble prepolymers) and catalysts into the dispersed phase (or continuous phase), and the core material is the dispersed phase. Since the reactive monomer (or soluble prepolymer) is soluble in a single phase, and its polymer is insoluble in the entire system such as the oil-in-water phase, the polymerization reaction of the soluble prepolymer occurs on the surface of the core material, so the reaction starts, the monomer is prepolymerized, and the prepolymer is polymerized. When the size of the prepolymer polymerization gradually increases, it is deposited on the surface of the core material.
[0050] Example 2
[0051] The polymer self-repairing material provided in this embodiment is a multi-layer network structure constructed by layer-by-layer self-assembly technology of epoxy resin layers with cross-linking density from low to high, each epoxy resin layer contains self-repairing microcapsules and anti-aging agent 2-hydroxy-4-methoxybenzophenone (BMDBM), the epoxy resin layer with the highest cross-linking density contains reinforcing filler glass fiber and compatibilizer DH-2, and the self-repairing microcapsules contain hydroxy silicate. 2-Hydroxy-4-methoxybenzophenone is an ultraviolet absorber, which can absorb ultraviolet rays and convert them into lower energy heat, thereby protecting the material from damage by ultraviolet rays.
[0052] The epoxy resin layer is formed by the cross-linking reaction of diepoxybutane and cystamine, each layer of the network structure is an epoxy resin layer, the epoxy resin layer with the highest cross-linking density is the outer layer of the multi-layer network structure, and the epoxy resin layer with the highest cross-linking density is formed by the cross-linking reaction of diepoxybutane and cystamine at 50-55°C, and the reaction condition is that the molar ratio of diepoxybutane to cystamine is 1:1; from the outer layer to the inner layer of the multi-layer network structure, the epoxy resin layer is also formed by the reaction of diepoxybutane and cystamine at 50-55°C, and the molar ratio of diepoxybutane to cystamine is greater than 1:1 layer by layer, and the cross-linking density of the formed epoxy resin layer decreases layer by layer.
[0053] The method for preparing the polymer self-healing material provided in this embodiment comprises the following steps:
[0054] S1. Using a plastic sheet as a base material, immersing an iron sheet in a dodecyl ammonium sulfate (DTAB) solution, pre-treating the plastic sheet so that the surface of the iron sheet carries a positive charge, and obtaining a pre-treated plastic sheet. Dodecyl ammonium sulfate is a cationic emulsifier. This type of emulsifier dissociates in water to form a positive charge. The emulsified product also carries a positive charge. The cross-linked epoxy resin layer also carries a corresponding charge. The epoxy resin layer can be self-assembled with the base material through electrostatic action.
[0055] S21, firstly prepare a urea-formaldehyde resin prepolymer, mix urea and formaldehyde in a molar ratio of 1:2, react under the conditions of pH 3 and temperature of 90°C for 1 hour to form a urea-formaldehyde resin prepolymer, the urea-formaldehyde resin prepolymer is a white precipitate of methylene urea, which is generated by the reaction of urea and formaldehyde. The prepared urea-formaldehyde resin prepolymer is very turbid and unstable, and cannot be cross-linked to obtain a water-insoluble polymer;
[0056] S22, using hydroxy silicate as the core material, dispersing it in water, adding sodium dodecyl sulfate (SDS) or ammonium dodecyl sulfate (DTAB) to form an aqueous solution; sodium dodecyl sulfate is an anionic emulsifier, which dissociates in water to form a negative charge; ammonium dodecyl sulfate is a cationic emulsifier, which dissociates in water to form a positive charge;
[0057] S23, using diepoxybutylene as the oil phase solution, slowly adding the aqueous phase solution to the oil phase solution under stirring to emulsify and form a water-in-oil emulsion;
[0058] S24, adding urea-formaldehyde resin prepolymer to a water-in-oil emulsion, and adding a curing agent, resorcinol, adjusting the solution pH to 8.5 to promote the cross-linking reaction of the urea-formaldehyde resin prepolymer itself, maintaining the reaction at a temperature of 60°C, and forming self-repairing microcapsules in a diepoxybutane solution. The unstable urea-formaldehyde resin prepolymer generates stable water-soluble hydroxymethyl urea in an alkaline environment. The prepared urea-formaldehyde resin prepolymer is viscous and transparent. The hydroxymethyl urea contains hydroxymethyl and imino groups. The core material is continuously polycondensed to obtain a non-water-soluble polymer with a cross-linked network structure, thereby obtaining self-repairing microcapsules;
[0059] S25, adding cystamine to the diepoxybutane solution at a molar ratio of diepoxybutane to cystamine of 5:1, and adding an anti-aging agent 2-hydroxy-4-methoxybenzophenone, stirring evenly, then immersing the pretreated plastic sheet into the solution, performing a cross-linking reaction at 55° C., curing to form a first epoxy resin layer on the pretreated plastic sheet, and washing unreacted diepoxybutane;
[0060] S3, according to the preparation method of the first epoxy resin layer, continue to prepare the second epoxy resin layer, and form multiple epoxy resin layers through electrostatic self-assembly until the outer layer of the multi-layer network structure, the electrostatic self-assembly is specifically: when the substrate material is positively charged after pretreatment, the preparation method of the first epoxy resin layer step S22 uses an anionic emulsifier with a negative charge, then the preparation method of the second epoxy resin layer step S22 uses a cationic emulsifier with a positive charge, and so on, until the outer layer of the multi-layer network structure, each epoxy resin layer is self-assembled by electrostatic self-assembly. A multilayer network structure is formed by self-assembly; the preparation method of the outer layer is different from that of the first epoxy resin layer in that the preparation method of the outer layer of the multilayer network structure is as follows: in step S25, after adding the anti-aging agent 2-hydroxy-4-methoxybenzophenone, reinforcing filler glass fiber and compatibilizer DH-2 are added, and stirred evenly, the molar ratio of diepoxybutane to cystamine is 1:1, and then the plastic sheet is immersed in the solution, a cross-linking reaction is carried out at 55°C, an outer layer of the multilayer network structure is formed on the plastic sheet, unreacted diepoxybutane is washed, and the mixture is dried to obtain a polymer self-healing material.
[0061] Example 3
[0062] The polymer self-healing material provided in this embodiment is a multi-layer network structure constructed by layer-by-layer self-assembly technology of epoxy resin layers with cross-linking density from low to high. Each epoxy resin layer contains self-healing microcapsules and anti-aging agent Tinuvin 770 (bis(1,2-benzisothiazolin-3,2') disulfide). The epoxy resin layer with the highest cross-linking density contains reinforcing filler carbon fiber and compatibilizer DH-2, and the self-healing microcapsules contain hydroxy silicate. Tinuvin 770 is a hindered amine light stabilizer (HALS), which is a very effective light stabilizer that can capture free radicals caused by light and prevent the occurrence of chain reactions.
[0063] The epoxy resin layer is formed by the cross-linking reaction of diepoxybutane and cystamine, each layer of the network structure is an epoxy resin layer, the epoxy resin layer with the highest cross-linking density is the outer layer of the multi-layer network structure, and the epoxy resin layer with the highest cross-linking density is formed by the cross-linking reaction of diepoxybutane and cystamine at 50-55°C, and the reaction condition is that the molar ratio of diepoxybutane to cystamine is 1:1; from the outer layer to the inner layer of the multi-layer network structure, the epoxy resin layer is also formed by the reaction of diepoxybutane and cystamine at 50-55°C, and the molar ratio of diepoxybutane to cystamine is greater than 1:1 layer by layer, and the cross-linking density of the formed epoxy resin layer decreases layer by layer.
[0064] The method for preparing the polymer self-healing material provided in this embodiment comprises the following steps:
[0065] S1. Using wood chips as substrate materials, immersing iron chips in a dodecyl ammonium sulfate (DTAB) solution, pre-treating the iron chips so that the surface of the wood chips carries a positive charge, and obtaining pre-treated wood chips. Dodecyl ammonium sulfate is a cationic emulsifier. This type of emulsifier dissociates in water to form positive charges. The emulsified product also carries a positive charge. The cross-linked epoxy resin layer also carries a corresponding charge. The epoxy resin layer can be self-assembled with the substrate material through electrostatic action.
[0066] S21, firstly prepare a urea-formaldehyde resin prepolymer, mix urea and formaldehyde in a molar ratio of 1:2, react under the conditions of pH 3 and temperature of 90°C for 1 hour to form a urea-formaldehyde resin prepolymer, the urea-formaldehyde resin prepolymer is a white precipitate of methylene urea, which is generated by the reaction of urea and formaldehyde. The prepared urea-formaldehyde resin prepolymer is very turbid and unstable, and cannot be cross-linked to obtain a water-insoluble polymer;
[0067] S22, using hydroxy silicate as the core material, dispersing it in water, adding sodium dodecyl sulfate (SDS) or ammonium dodecyl sulfate (DTAB) to form an aqueous solution; sodium dodecyl sulfate is an anionic emulsifier, which dissociates in water to form a negative charge; ammonium dodecyl sulfate is a cationic emulsifier, which dissociates in water to form a positive charge;
[0068] S23, diepoxybutylene as the oil phase solution, under stirring conditions, slowly adding the aqueous phase solution to the oil phase solution for emulsification to form a water-in-oil emulsion;
[0069] S24, adding urea-formaldehyde resin prepolymer to a water-in-oil emulsion, and adding a curing agent, resorcinol, adjusting the pH value of the solution to 9 to promote the cross-linking reaction of the urea-formaldehyde resin prepolymer itself, maintaining the reaction at a temperature of 60°C, and forming self-repairing microcapsules in a diepoxybutane solution. The unstable urea-formaldehyde resin prepolymer generates stable water-soluble hydroxymethyl urea in an alkaline environment. The prepared urea-formaldehyde resin prepolymer is viscous and transparent. The hydroxymethyl urea contains hydroxymethyl and imino groups. The core material is continuously polycondensed to obtain a non-water-soluble polymer with a cross-linked network structure, thereby obtaining self-repairing microcapsules;
[0070] S25, adding cystamine to the diepoxybutane solution at a molar ratio of diepoxybutane to cystamine of 5:1, and adding an anti-aging agent Tinuvin 770, stirring evenly, then immersing the pretreated wood chips in the solution, performing a cross-linking reaction at 53° C., curing to form a first epoxy resin layer on the pretreated wood chips, and washing unreacted diepoxybutane;
[0071] S3. According to the preparation method of the first epoxy resin layer, continue to prepare the second epoxy resin layer, and form multiple epoxy resin layers through electrostatic self-assembly until the outer layer of the multi-layer network structure. The electrostatic self-assembly is specifically: when the substrate material is positively charged after pretreatment, an anionic emulsifier with a negative charge is used in the preparation method of the first epoxy resin layer step S22, then a cationic emulsifier with a positive charge is used in the preparation method of the second epoxy resin layer step S22, and so on, until the outer layer of the multi-layer network structure, each epoxy resin layer self-assembles through electrostatic action to form a multi-layer network structure; the preparation method of the outer layer is different from that of the first epoxy resin layer in that the preparation method of the outer layer of the multi-layer network structure is to add an anti-aging agent Tinuvin in step S25. After 770, reinforcing filler carbon fiber and compatibilizer DH-2 are added and stirred evenly. The molar ratio of diepoxybutane and cystamine is 1:1. Then, the wood chips are immersed in the solution and cross-linked at 53°C to form an outer layer of a multi-layer network structure on the wood chips. The unreacted diepoxybutane is washed and dried to obtain a polymer self-healing material.
[0072] Example 4
[0073] The polymer self-repairing material provided in this embodiment is a multilayer network structure constructed by layer-by-layer self-assembly technology of epoxy resin layers with cross-linking density from low to high. Each layer of epoxy resin contains self-repairing microcapsules and anti-aging agent butylated hydroxytoluene. The epoxy resin layer with the highest cross-linking density contains reinforcing filler carbon fiber and compatibilizer DH-2, and the self-repairing microcapsules contain hydroxy silicate and thiol oxidant iodine element. Butylated hydroxytoluene is a bisphenol A type antioxidant. This type of antioxidant can delay or inhibit the process of degradation of materials by atmospheric oxygen during polymerization, storage, transportation, processing, and use, thereby preventing material aging and extending service life. As a widely used oxidant, iodine can catalyze the oxidation of thiols to generate disulfides.
[0074] The epoxy resin layer is formed by the cross-linking reaction of diepoxybutane and cystamine, each layer of the network structure is an epoxy resin layer, the epoxy resin layer with the highest cross-linking density is the outer layer of the multi-layer network structure, and the epoxy resin layer with the highest cross-linking density is formed by the cross-linking reaction of diepoxybutane and cystamine at 50-55°C, and the reaction condition is that the molar ratio of diepoxybutane to cystamine is 1:1; from the outer layer to the inner layer of the multi-layer network structure, the epoxy resin layer is also formed by the reaction of diepoxybutane and cystamine at 50-55°C, and the molar ratio of diepoxybutane to cystamine is greater than 1:1 layer by layer, and the cross-linking density of the formed epoxy resin layer decreases layer by layer.
[0075] The method for preparing the polymer self-healing material provided in this embodiment comprises the following steps:
[0076] S1. Using an iron sheet as a base material, immersing the iron sheet in a dodecyl ammonium sulfate (DTAB) solution, pre-treating the iron sheet so that the surface of the iron sheet carries a positive charge, and obtaining a pre-treated iron sheet. Dodecyl ammonium sulfate is a cationic emulsifier. This type of emulsifier dissociates in water to form a positive charge. The emulsified product also carries a positive charge. The cross-linked epoxy resin layer also carries a corresponding charge. The epoxy resin layer can be self-assembled with the base material through electrostatic action.
[0077] S21, firstly prepare a urea-formaldehyde resin prepolymer, mix urea and formaldehyde in a molar ratio of 1:2, react under the conditions of pH 3 and temperature of 90°C for 1 hour to form a urea-formaldehyde resin prepolymer, the urea-formaldehyde resin prepolymer is a white precipitate of methylene urea, which is generated by the reaction of urea and formaldehyde. The prepared urea-formaldehyde resin prepolymer is very turbid and unstable, and cannot be cross-linked to obtain a water-insoluble polymer;
[0078] S22, using hydroxy silicate and thiol oxidant iodine as core materials, dispersed in water, adding sodium dodecyl sulfate (SDS) or ammonium dodecyl sulfate (DTAB) to form an aqueous solution; sodium dodecyl sulfate is an anionic emulsifier, which dissociates in water to form a negative charge; ammonium dodecyl sulfate is a cationic emulsifier, which dissociates in water to form a positive charge;
[0079] S23, using diepoxybutylene as the oil phase solution, slowly adding the aqueous phase solution to the oil phase solution under stirring to emulsify and form a water-in-oil emulsion;
[0080] S24, adding urea-formaldehyde resin prepolymer to a water-in-oil emulsion, and adding a curing agent, resorcinol, adjusting the pH value of the solution to 8 to promote the cross-linking reaction of the urea-formaldehyde resin prepolymer itself, maintaining the reaction at a temperature of 60° C., forming self-repairing microcapsules in a diepoxybutane solution, and the unstable urea-formaldehyde resin prepolymer generates stable water-soluble hydroxymethyl urea in an alkaline environment. The prepared urea-formaldehyde resin prepolymer is viscous and transparent, and the hydroxymethyl urea contains hydroxymethyl and imino groups. The core material is continuously polycondensed to obtain a non-water-soluble polymer with a cross-linked network structure, thereby obtaining a self-repairing microcapsule;
[0081] S25, adding cystamine to the diepoxybutane solution according to a molar ratio of diepoxybutane to cystamine of 5:1, and adding an anti-aging agent, stirring evenly, then immersing the pretreated iron sheet into the solution, performing a cross-linking reaction at 50° C., curing to form a first epoxy resin layer on the pretreated iron sheet, and washing unreacted diepoxybutane;
[0082] S3, according to the preparation method of the first epoxy resin layer, continue to prepare the second epoxy resin layer, and form multiple epoxy resin layers through electrostatic self-assembly until the outer layer of the multi-layer network structure, the electrostatic self-assembly is specifically: when the substrate material is positively charged after pretreatment, the preparation method of the first epoxy resin layer step S22 uses an anionic emulsifier with a negative charge, then the preparation method of the second epoxy resin layer step S22 uses a cationic emulsifier with a positive charge, and so on, until the outer layer of the multi-layer network structure, each epoxy resin layer is positively charged. The epoxy resin layer self-assembles to form a multi-layer network structure through electrostatic action; the preparation method of the outer layer is different from that of the first epoxy resin layer. The preparation method of the outer layer of the multi-layer network structure is that in step S25, after adding an anti-aging agent, reinforcing filler carbon fiber and compatibilizer DH-2 are added, and stirred evenly. The molar ratio of diepoxybutane and cystamine is 1:1, and then the iron sheet is immersed in the solution, and a cross-linking reaction is carried out at 50°C to form an outer layer of the multi-layer network structure on the iron sheet, and the unreacted diepoxybutane is washed and dried to obtain a polymer self-healing material.
[0083] In this embodiment, the self-repairing microcapsule may further include a thiol oxidant, which can catalyze the formation of disulfide bonds and improve the repair efficiency of reversible disulfide bonds. The thiol oxidant may also be potassium permanganate or manganese dioxide.
[0084] Comparative Example 1
[0085] In this comparative example, the iron sheet is used as the base material, and the polymer self-repairing material of Example 1 is not coated on the surface of the iron sheet.
[0086] Comparative Example 2
[0087] The polymer self-repairing material provided in this comparative example is a multi-layer network structure constructed by layer-by-layer self-assembly technology of epoxy resin layers with cross-linking density from low to high, each epoxy resin layer contains self-repairing microcapsules and butylated hydroxytoluene, an anti-aging agent, and the epoxy resin layer with the highest cross-linking density contains reinforcing filler carbon fiber and compatibilizer DH-2, and the self-repairing microcapsules contain hydroxy silicate. Butylated hydroxytoluene is a bisphenol A type antioxidant, which can delay or inhibit the degradation of materials due to atmospheric oxygen during polymerization, storage, transportation, processing, and use, thereby preventing material aging and extending service life.
[0088] The method for preparing the polymer self-healing material provided in this embodiment comprises the following steps:
[0089] S1. Using an iron sheet as a base material, immersing the iron sheet in a dodecyl ammonium sulfate (DTAB) solution, pre-treating the iron sheet so that the surface of the iron sheet carries a positive charge, and obtaining a pre-treated iron sheet. Dodecyl ammonium sulfate is a cationic emulsifier. This type of emulsifier dissociates in water to form a positive charge. The emulsified product also carries a positive charge. The cross-linked epoxy resin layer also carries a corresponding charge. The epoxy resin layer can be self-assembled with the base material through electrostatic action.
[0090] S21, firstly prepare a urea-formaldehyde resin prepolymer, mix urea and formaldehyde in a molar ratio of 1:2, react under the conditions of pH 3 and temperature of 90°C for 1 hour to form a urea-formaldehyde resin prepolymer, the urea-formaldehyde resin prepolymer is a white precipitate of methylene urea, which is generated by the reaction of urea and formaldehyde. The prepared urea-formaldehyde resin prepolymer is very turbid and unstable, and cannot be cross-linked to obtain a water-insoluble polymer;
[0091] S22, using hydroxy silicate as the core material, dispersing it in water, adding sodium dodecyl sulfate (SDS) or ammonium dodecyl sulfate (DTAB) to form an aqueous solution; sodium dodecyl sulfate is an anionic emulsifier, which dissociates in water to form a negative charge; ammonium dodecyl sulfate is a cationic emulsifier, which dissociates in water to form a positive charge;
[0092] S23, diepoxybutylene as the oil phase solution, under stirring conditions, slowly adding the aqueous phase solution to the oil phase solution for emulsification to form a water-in-oil emulsion;
[0093] S24, adding urea-formaldehyde resin prepolymer to a water-in-oil emulsion, and adding a curing agent, resorcinol, adjusting the pH value of the solution to 8 to promote the cross-linking reaction of the urea-formaldehyde resin prepolymer itself, maintaining the reaction at a temperature of 60° C., forming self-repairing microcapsules in a diepoxybutane solution, and the unstable urea-formaldehyde resin prepolymer generates stable water-soluble hydroxymethyl urea in an alkaline environment. The prepared urea-formaldehyde resin prepolymer is viscous and transparent, and the hydroxymethyl urea contains hydroxymethyl and imino groups. The core material is continuously polycondensed to obtain a non-water-soluble polymer with a cross-linked network structure, thereby obtaining a self-repairing microcapsule;
[0094] S25, adding cystamine to the diepoxybutane solution in a molar ratio of diepoxybutane to cystamine of 1:1, and adding butyl hydroxytoluene (an anti-aging agent), stirring evenly, then immersing the pretreated substrate material in the solution, performing a cross-linking reaction at 50° C., curing to form a first epoxy resin layer on the pretreated substrate material, and washing unreacted diepoxybutane;
[0095] S3, according to the preparation method of the first epoxy resin layer, continue to prepare the second epoxy resin layer, and form multiple epoxy resin layers through electrostatic self-assembly until the outer layer of the multi-layer network structure, the electrostatic self-assembly is specifically: when the substrate material is positively charged after pretreatment, the preparation method of the first epoxy resin layer step S22 uses an anionic emulsifier with a negative charge, then the preparation method of the second epoxy resin layer step S22 uses a cationic emulsifier with a positive charge, and so on, until the outer layer of the multi-layer network structure, each epoxy resin layer is self-assembled. The outer layer is self-assembled through electrostatic action to form a multilayer network structure; the preparation method of the outer layer is different from that of the first epoxy resin layer. The preparation method of the outer layer of the multilayer network structure is that in step S25, after adding the anti-aging agent butylhydroxytoluene, the reinforcing filler carbon fiber and the compatibilizer DH-2 are added, and stirred evenly. The molar ratio of diepoxybutane and cystamine is 1:1, and then the base material is immersed in the solution, and a cross-linking reaction is carried out at 50°C to form an outer layer of the multilayer network structure on the base material, and the unreacted diepoxybutane is washed and dried to obtain a polymer self-healing material.
[0096] Comparative Example 3
[0097] The polymer self-repairing material provided in this comparative example is a multi-layer network structure constructed by layer-by-layer self-assembly technology of epoxy resin layers with cross-linking density from low to high, each epoxy resin layer contains self-repairing microcapsules and butylated hydroxytoluene, an anti-aging agent, and the epoxy resin layer with the highest cross-linking density contains reinforcing filler carbon fiber and compatibilizer DH-2, and the self-repairing microcapsules contain hydroxy silicate. Butylated hydroxytoluene is a bisphenol A type antioxidant, which can delay or inhibit the degradation of materials due to atmospheric oxygen during polymerization, storage, transportation, processing, and use, thereby preventing material aging and extending service life.
[0098] The method for preparing the polymer self-healing material provided in this embodiment comprises the following steps:
[0099] S1. Using an iron sheet as a base material, immersing the iron sheet in a sodium dodecyl sulfate (SDS) solution, pre-treating the iron sheet so that the surface of the iron sheet carries a positive charge, and obtaining a pre-treated iron sheet. Sodium dodecyl sulfate is a cationic emulsifier. This type of emulsifier dissociates in water to form a positive charge. The emulsified product also carries a positive charge. The cross-linked epoxy resin layer also carries a corresponding charge. The epoxy resin layer can be self-assembled with the base material through electrostatic action.
[0100] S2, adding cystamine to the diepoxybutane solution in a molar ratio of diepoxybutane to cystamine of 1:1, and adding butyl hydroxytoluene (an anti-aging agent), stirring evenly, then immersing the pretreated substrate material in the solution, performing a cross-linking reaction at 50° C., curing to form a first epoxy resin layer on the pretreated substrate material, and washing unreacted diepoxybutane;
[0101] S3, according to the preparation method of the first epoxy resin layer, continue to prepare the second epoxy resin layer, and form multiple epoxy resin layers through electrostatic self-assembly until the outer layer of the multi-layer network structure, the electrostatic self-assembly is specifically: when the substrate material is positively charged after pretreatment, the preparation method of the first epoxy resin layer step S22 uses an anionic emulsifier with a negative charge, then the preparation method of the second epoxy resin layer step S22 uses a cationic emulsifier with a positive charge, and so on, until the outer layer of the multi-layer network structure, each epoxy resin layer is self-assembled. The outer layer is self-assembled through electrostatic action to form a multilayer network structure; the preparation method of the outer layer is different from that of the first epoxy resin layer. The preparation method of the outer layer of the multilayer network structure is that in step S25, after adding the anti-aging agent butylhydroxytoluene, the reinforcing filler carbon fiber and the compatibilizer DH-2 are added, and stirred evenly. The molar ratio of diepoxybutane and cystamine is 1:1, and then the base material is immersed in the solution, and a cross-linking reaction is carried out at 50°C to form an outer layer of the multilayer network structure on the base material, and the unreacted diepoxybutane is washed and dried to obtain a polymer self-healing material.
[0102] Experimental example
[0103] Scratch repair experiment
[0104] The scratch repair experiment was conducted on a polarized optical microscope (POM) equipped with a heating stage and a UCMOS05100KPA (P / N: TP605100A) microscope camera. The iron sheet materials provided in Example 1 and Comparative Examples 1-3 were placed side by side, and a scratch was made on the surface of the iron sheet using four knives provided by the equipment. The width of the scratch was about 40 μm. The self-healing behavior of the materials provided in Example 1 and Comparative Examples 1-3 was observed under a microscope, and photographed and recorded. The results are shown in FIG. Figure 1 shown.
[0105] The results show that the scratches on the surface of the iron sheet material in Example 1 basically disappear after repair, the leveling is good and no interface phase refraction occurs. The scratches on the surface of the iron sheet material in Comparative Example 1 remain the same. Unlike Example 1, the multilayer network structure formed in Comparative Example 2 has the highest cross-linking density of each epoxy resin layer, and the multilayer network structure formed in Comparative Example 3 has the highest cross-linking density of each epoxy resin layer, and each epoxy resin layer does not contain self-repairing microcapsules. It can be seen from the figure that Comparative Example 2 and Comparative Example 2 have certain self-healing behavior, but the repair effect of Comparative Example 3 is poor, indicating that the multilayer network structure of Example 1 is composed of epoxy resins with cross-linking density from low to high. The resin layer is constructed by layer-by-layer self-assembly technology, and the self-repairing microcapsules are evenly dispersed in each layer of epoxy resin layer. When the surface of the iron sheet is damaged, cracks are generated at the damaged part, and the self-repairing microcapsules are broken under stress. The self-repairing microcapsules at other positions of the damaged part and other layers of epoxy resin layers can still easily migrate to the damaged part, improving the repair efficiency and repair effect of the self-repairing microcapsules at the damaged part, thereby solving the problem that the third-generation self-repairing polymer can achieve multiple repairs, but the repair agent is unevenly distributed in the polymer network, the content of the repair agent inside the microcapsule is limited, and it does not have a recycling function, and it is impossible to achieve multiple self-repair of the material. In Example 1, self-repairing microcapsules are contained, and hydroxyl groups are formed after the epoxy group is opened. After the self-repairing microcapsules are broken, the released hydroxy silicate can react with the hydroxyl group, increase the reaction sites of the healing surface of the damaged part, improve the repair efficiency of the reversible disulfide bonds in the epoxy resin, and strengthen the repair effect of the reversible disulfide bonds. Therefore, it can solve the problem that when the material is repeatedly damaged, there are few reaction sites on the healing surface, resulting in insufficient diffusion of the molecular chain, and the self-healing efficiency decreases slightly after each cutting healing cycle.
[0106] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A polymer self-healing material, characterized in that: It is a multi-layer network structure constructed by layer-by-layer self-assembly technology of epoxy resin layers with cross-linking density from low to high. Each epoxy resin layer contains self-repairing microcapsules and anti-aging agents. The epoxy resin layer with the highest cross-linking density contains reinforcing fillers and compatibilizers. In each epoxy resin layer, the self-repairing microcapsules are prepared by in-situ polymerization method. The specific preparation steps are as follows: S1, first preparing a urea-formaldehyde resin prepolymer, mixing urea and formaldehyde in proportion, reacting at a pH value of 3 and a temperature of 90° C. for 1 hour to form the urea-formaldehyde resin prepolymer; S2, using hydroxy silicate as the core material, dispersing it in water, adding an emulsifier, and forming an aqueous solution; S3, using diepoxybutylene as the oil phase solution, and slowly adding the water phase solution to the oil phase solution under stirring to emulsify and form a water-in-oil emulsion; S4. Add the urea-formaldehyde resin prepolymer to the water-in-oil emulsion, add a curing agent, adjust the pH value of the solution to an alkaline environment to promote the cross-linking reaction of the urea-formaldehyde resin prepolymer itself, maintain the reaction at a temperature of 60° C., and form the self-healing microcapsules in the diepoxybutylene solution.
2. The polymer self-healing material according to claim 1, characterized in that: The reinforcing filler is carbon fiber or glass fiber.
3. The polymer self-healing material according to claim 1, characterized in that: The compatibilizer is DH-2.
4. The polymer self-healing material according to claim 1, characterized in that: The epoxy resin layer is formed by the cross-linking reaction of diepoxybutane and cystamine, and each layer of the network structure is an epoxy resin layer. The epoxy resin layer with the highest cross-linking density is the outer layer of the multi-layer network structure. The epoxy resin layer with the highest cross-linking density is formed by the cross-linking reaction of diepoxybutane and cystamine at 50-55°C, and the reaction condition is that the molar ratio of the diepoxybutane to the cystamine is 1:1; from the outer layer to the inner layer of the multi-layer network structure, the epoxy resin layer is also formed by the reaction of the diepoxybutane and the cystamine at 50-55°C, and the molar ratio of the diepoxybutane to the cystamine is greater than 1:1 layer by layer, and the cross-linking density of the formed epoxy resin layer decreases layer by layer.
5. The polymer self-healing material according to claim 4, characterized in that: The self-repairing microcapsules are evenly dispersed in each epoxy resin layer.
6. The polymer self-healing material according to claim 5, characterized in that: After the self-repairing microcapsules are formed in the diepoxybutane solution, the cystamine is added to the diepoxybutane solution according to the molar ratio of the diepoxybutane to the cystamine, stirred evenly, and cross-linked at 50-55° C. to obtain each epoxy resin layer.
7. The method for preparing the polymer self-repairing material according to claim 6, characterized in that: The following steps are involved: S1, immersing the base material in an ionic emulsifier solution to pretreat the base material to obtain a pretreated base material; S21, first preparing a urea-formaldehyde resin prepolymer, mixing urea and formaldehyde in proportion, reacting at a pH value of 3 and a temperature of 90° C. for 1 hour to form the urea-formaldehyde resin prepolymer; S22, using hydroxy silicate as the core material, dispersing it in water, adding ionic emulsifiers of different charge types to form an aqueous solution; S23, using diepoxybutylene as the oil phase solution, slowly adding the aqueous phase solution into the aqueous phase solution under stirring conditions, emulsifying to form a water-in-oil emulsion; S24, adding the urea-formaldehyde resin prepolymer to the water-in-oil emulsion, adding a curing agent, adjusting the pH value of the solution to an alkaline environment to promote the cross-linking reaction of the urea-formaldehyde resin prepolymer, maintaining the reaction at a temperature of 60° C., and forming the self-healing microcapsules in the diepoxybutylene solution; S25, adding cystamine to the diepoxybutane solution according to the molar ratio of diepoxybutane to the cystamine, and adding the anti-aging agent, stirring evenly, the molar ratio of diepoxybutane to the cystamine is greater than 1:1; then immersing the pretreated substrate material into the solution, performing a cross-linking reaction at 50-55° C., curing to form a first layer of the epoxy resin layer on the pretreated substrate material, and washing unreacted diepoxybutane; S3. According to the preparation method of the first epoxy resin layer, continue to prepare the second epoxy resin layer, and form a multi-layer epoxy resin layer through electrostatic self-assembly until the outer layer of the multi-layer network structure. The outer layer is different from the preparation method of the first epoxy resin layer in that the preparation method of the outer layer of the multi-layer network structure is as follows: in step S25, after adding the anti-aging agent, add the reinforcing filler and the compatibilizer, stir evenly, and the molar ratio of the diepoxybutane to the cystamine is 1:1; then continue to immerse the base material in the solution, carry out a cross-linking reaction at 50-55°C, form the outer layer of the multi-layer network structure on the base material, wash the unreacted diepoxybutane, and obtain the polymer self-healing material.
8. The method for preparing a polymer self-repairing material according to claim 7, characterized in that: The base material is metal, wood or plastic.
9. The method for preparing a polymer self-repairing material according to claim 7, characterized in that: In step S22, a thiol oxidant may be added and dispersed in water together with the hydroxy silicate as a core material.
Citation Information
Patent Citations
Multi-layer structure assembly
CN113978071A